INTERNALISASI NILAI-NILAI KEARIFAN LOKAL PADA PELAJARAN BAHASA JAWA DI SEKOLAH DASAR - Haryanti, Yanti; Kaltsum, Honest Ummi (Profesi Pendidikan Dasar, 2019)
Local wisdom is supposed to be a basic guideline for people to live their life in the surround society. Recently, media emerges and discusses on the survival of the local wisdom throughout the Indonesian society. This research is trying to review how the values of local wisdom are taught in elementrary schools. Process of learning cultural values is better done intensively and continuously that internalization of the values can be absorbed well. Internalization process of the values done in schools need tough efforts, started with selection of media or tools which load the values needed to be learned. Using the content analysis, this research is trying to review the content about local wisdom in the text books of Bahasa Jawa subject. This analysis is hoped to find themes and examples of the implementation of the Javanesse local wisdom. By using the content analysis, this research results in the findings that the three dimensions of local values are covered in all text books used in the research; however, there are some detail values found undiscussed in the text books. Â